Digital Technologies in the Process of Virtualization of Consumer Behaviour - Awareness of New Technologies = Technologie cyfrowe w procesie wirtualizacji zachowań konsumentów - Kaczorowska-Spychalska, Dominika (Zielona Góra: Faculty of Economics and Management Press)
Digital resolution is currently one of the most important forces determining changes and their dynamics in the social, cultural and economic dimension. Digital technologies such as the Internet of Things and Artificial Intelligence will, according to Gartner's Hype Cycle for Emerging Technologies 2017, play an increasingly important role while creating a new quality of the market space.
Keywords: technologie cyfrowe; internet rzeczy; sztuczna inteligencja; zachowania konsumenckie; digital technologies; Internet of Things (IoT); artificial intelligence; consumer behaviour